Performance evaluation of holonic control of a switch arrival system. (March 2017) - Indriago, Carlos; Cardin, Olivier; Bellenguez-Morineau, Odile; Rakoto, Naly; Castagna, Pierre; Chacòn, Edgar
The application of holonic paradigm to the hybrid control system class is a promising way to give flexibility to the control of such systems, leading to new industrial intelligent processes. However, there is a need for performance evaluation of such solutions in order to give them credit among the multiple formalisms used in the literature. This article aims at evaluating the optimality and stability of the holonic control of a switch arrival system, a classical system from the literature where a unique server has to switch between leaking tanks full of fluids before they get empty. Optimality is evaluated compared to a scheduling algorithm aimed at minimizing the number of switches of the server while respecting the constraints. Stability is evaluated through a stochastic simulation run aiming at finding cyclic behavior of the control in a whole set of random initial configurations. The results tend to show a good overall performance of the control, especially considering the algorithms used are quite simple, thus could be made better and enhance the performance.